Fragmentation of 120 and 200 MeV u−14He ions in water and PMMA targets. (23rd January 2017) - Rovituso, M; Schuy, C; Weber, U; Brons, S; Cortés-Giraldo, M A; La Tessa, C; Piasetzky, E; Izraeli, D; Schardt, D; Toppi, M; Scifoni, E; Krämer, M; et al.
Abstract: Recently, the use of 4 He particles in cancer radiotherapy has been reconsidered as they potentially represent a good compromise between protons and 12 C ions. The first step to achieve this goal is the development of a dedicated treatment planning system, for which basic physics information such as the characterization of the beam lateral scattering and fragmentation cross sections are required. In the present work, the attenuation of 4 He primary particles and the build-up of secondary charged fragments at various depths in water and polymethyl methacrylate were investigated experimentally for 120 and 200 MeV u −1 beams delivered by the synchrotron at the Heidelberg Ion-Beam Therapy Center, Heidelberg. Species and isotope identification was accomplished combining energy loss and time-of-flight measurements. Differential yields and energy spectra of all fragments types were recorded between 0° and 20° with respect to the primary beam direction.